The Effectiveness of Using Electronic Modules in Mathematics Subjects in the Material of Constructing Flat Sided Space - Maulana, Muhammad Natsir; Muslim, Suyitno; Sukardjo, Moch (Journal of Education Reseach and Evaluation, 2022)
Current technological developments encourage the development of many electronic modules that affect the learning process. The problem of learning mathematics obtained lies in learning outcomes that are not optimal, one of the causes is the lack of learning resources and limited study time. This study aimed to analyze the effectiveness of the electronic module on cognitive learning outcomes in the side-plane material. The research approach used is quantitative. The type of research used is pre-experimental research. The design used in this research is One Group Pretest-Posttest. The subjects of this study were class VIII students, who collected 32 students consisting of 14 boys and 18 girls. Methods of data collection by observation, interviews, and tests. The test instrument used was an objective test with 10 items. The analysis of improving learning outcomes was analyzed using the N-Gain formula. N-Gain is used to improve learning outcomes. Based on the N-gain analysis, student learning outcomes show a value of 0.61 or, in percentage, 61%, with a reasonably practical category. It was concluded that learning using the electronic mathematics module was quite effective in improving students' mathematics learning outcomes. E-modules can help students in learning.